2021
DOI: 10.1016/j.rasd.2020.101711
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about home education and autism? A thematic synthesis review

Abstract: This is a repository copy of What do we know about home education and autism? A thematic synthesis review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 48 publications
(88 reference statements)
6
25
0
Order By: Relevance
“…In most cases, students were reported as more engaged, their learning increased, and improvements were noted in behaviour and mental health, which is consistent with prior research (see O'Hagan et al, 2021), but findings were more mixed with regard to students becoming independent learners. While some students developed friendships through online exchanges and improvements in social skills were observed, there was also the view of some parents that students may be missing out on the opportunity for face-to-face interactions.…”
Section: Benefits Challenges and Outcomessupporting
confidence: 87%
See 2 more Smart Citations
“…In most cases, students were reported as more engaged, their learning increased, and improvements were noted in behaviour and mental health, which is consistent with prior research (see O'Hagan et al, 2021), but findings were more mixed with regard to students becoming independent learners. While some students developed friendships through online exchanges and improvements in social skills were observed, there was also the view of some parents that students may be missing out on the opportunity for face-to-face interactions.…”
Section: Benefits Challenges and Outcomessupporting
confidence: 87%
“…It is unsurprising therefore that some parents choose to remove their autistic child from mainstream schooling and seek alternative educational options, such as home education. In a recent review, five key motivations were identified: a school's lack of flexible and inclusive practices, school staff's insufficient understanding of autism, the exclusionary nature of mainstream school, experiences of bullying, and their child's subsequent mental health issues (O'Hagan et al, 2021). Included in this review were the only two Australian studies examining the experiences of mothers home educating their autistic children (i.e., Kidd & Kaczmarek, 2010;McDonald & Lopes, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, it is possible that teachers were struggling themselves with coping with the pandemic and/or simply did not know how best to support autistic children remotely, especially when children began to disengage with online learning. Given that educators’ level of knowledge and understanding of autism – as reported by both teachers and parents – is one potential explanation for poorer autistic student outcomes (Anderson, 2020; Majoko, 2016; O’Hagan et al, 2021; Roberts & Simpson, 2016), it is plausible that teachers might simply not have known what tangible steps to take to support their autistic students effectively at a distance (Haspel & Lauderdale-Littin, 2020). They might also have relied too heavily on stereotypes about autism, mistakenly assuming that their autistic students could not, or did not want, to connect with their teachers and peers during this time.…”
Section: Discussionmentioning
confidence: 99%
“…The only impact noted by parents of children who were home-schooled both before and during COVID-19 restrictions was a reduction in the number of extracurricular activities that could be undertaken due to shutdowns. This may have been particularly notable for this group of children given that home-educated children are reported to be more involved in extracurricular and social activities than those in mainstream education (for a review on home-schooling in autism see O’Hagan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%